Claus Kreß & Stefan Barriga (Eds.) (2017) The Crime of Aggression: A Commentary. Cambridge: Cambridge University Press (2018)
Reseña Bibliográfica del libro Claus Kreß & Stefan Barriga (Eds.) (2017). The Crime of Aggression: A Commentary. Cambridge: Cambridge University Press